2016
DOI: 10.1126/scitranslmed.aaf4964
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive low-level laser therapy for thrombocytopenia

Abstract: Thrombocytopenia is a common hematologic disorder that is managed primarily by platelet transfusions. We report here that noninvasive whole-body illumination with a special near-infrared laser cures acute thrombocytopenia triggered by g-irradiation within 2 weeks in mice, as opposed to a 5-week recovery time required in controls. The low-level laser (LLL) also greatly accelerated platelet regeneration in the presence of anti-CD41 antibody that binds and depletes platelets, and prevented a severe drop in platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 40 publications
3
57
1
Order By: Relevance
“…Our recent study showed that LLLT bolstered ATP production and mitochondrial biogenesis in MKs18. Whether or not this held true in the presence of anti-CD41 antibody remained unknown.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Our recent study showed that LLLT bolstered ATP production and mitochondrial biogenesis in MKs18. Whether or not this held true in the presence of anti-CD41 antibody remained unknown.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, we discovered that 810-nm continuous wave diode laser at 30 J/cm 2 could penetrate into mouse bone marrow noninvasively without incurring any significant heat18. Noninvasive whole body illuminations with the LLLT cured acute thrombocytopenia induced by irradiation, chemotherapeutic drug, or anti-CD41 antibody much faster than sham-light treatment18. We found that LLLT bolstered mitochondrial biogenesis predominantly in polyploid megakaryocytes (MKs), increasing platelet production both in vivo and in vitro 18.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigators, including us, have shown that low-level light treatment (LLLT) modulates ATP production, reactive oxygen species (ROS) formation, apoptosis, cellular metabolic process, and signaling transduction pathways secondarily Scientific RepoRts | 6:38238 | DOI: 10.1038/srep38238 to more sufficient function of mitochondria under various conditions of stress [15][16][17] . Recently, we discovered that 810-nm continuous wave diode laser at 30 J/cm 2 could penetrate into mouse bone marrow noninvasively without incurring any significant heat 18 . Noninvasive whole body illuminations with the LLLT cured acute thrombocytopenia induced by irradiation, chemotherapeutic drug, or anti-CD41 antibody much faster than sham-light treatment 18 .…”
mentioning
confidence: 99%